2017
DOI: 10.1016/j.geomorph.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Are restored side channels sustainable aquatic habitat features? Predicting the potential persistence of side channels as aquatic habitats based on their fine sedimentation dynamics

Abstract: International audienceThe restoration of side channels (also referred to as abandoned channels, former channels, floodplain channels, or side arms) is increasingly implemented to improve the ecological integrity of river-floodplain systems. However, the design of side channel restoration projects remains poorly informed by theory or empirical observations despite the increasing number of projects. Moreover, feedback regarding the hydromorphological adjustment of restored channels is rarely documented, making i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…17B). An exponential function seems reasonable because the initial bed level change is large and with increasing bed level the sediment supply is expected to decrease until it reaches a bed level height from which much smaller floodplain aggradation rates occur (Riquier et al, 2017;Van Denderen et al, 2018a). The exponential function suggests that this bed level height is reached when the bevel change is between 1.3 and 1.4 m y=0.9(1-e -(x-6.75)/9.9 )+0.5 ( Fig.…”
Section: Bed Levelmentioning
confidence: 99%
“…17B). An exponential function seems reasonable because the initial bed level change is large and with increasing bed level the sediment supply is expected to decrease until it reaches a bed level height from which much smaller floodplain aggradation rates occur (Riquier et al, 2017;Van Denderen et al, 2018a). The exponential function suggests that this bed level height is reached when the bevel change is between 1.3 and 1.4 m y=0.9(1-e -(x-6.75)/9.9 )+0.5 ( Fig.…”
Section: Bed Levelmentioning
confidence: 99%
“…It is well known that artificial side channels generally aggrade (e.g., Formann, Habersack, & Schober, ; Riquier, Piégay, Lamouroux, & Vaudor, ; Simons et al, ; Van Denderen, Schielen, Westerhof, Quartel, & Hulscher, ). Within one river branch, side channels aggrade at various rates and with various types of sediment (Riquier, Piégay, & Michalkova, ; Riquier et al, ; Van Denderen et al, ). There is a need for a better understanding of the mechanisms and the processes that result in the aggradation of such side channels.…”
Section: Introductionmentioning
confidence: 99%
“…The flow separation zone captures sediment at the entrance of the channel which in case of a limited transport capacity can enhance the growth of a plug bar (Constantine et al, 2010;Dieras et al, 2013). After the formation of a plug bar, sediment can still enter the channel at the confluence and during water level variations this can lead to the deposition of fines in the channel (Citterio and Piégay, 2009;Riquier et al, 2017). From the moment that the meander is disconnected from the main channel, the filling-in of the channel occurs with fine material during overbank flow conditions (Makaske et al, 2002;Constantine et al, 2010;Toonen et al, 2012).…”
Section: Development Of Side Channelsmentioning
confidence: 99%
“…This has resulted in more than 20 side channels in the Rhine branches that are connected to the main channel at both their upstream and downstream end ( Figure 1.1 ). It is found that almost all constructed side channels aggrade (Simons et al, 2001;Formann et al, 2007;Riquier et al, 2017). A better understanding of the mechanisms that cause 0 1 aggradation may lead to a more optimal design of side channels and a reduction of the maintenance costs.…”
Section: Samenvatting Introductionmentioning
confidence: 99%
See 1 more Smart Citation